Ciri-ciri Kepribadian David Kim Dalam Film “Searching” Disutradarai oleh Aneesh Chaganty - Siska, Siska; Irpan Ali Rahman (e-LinguaTera, 2025)
This research is entitled "David Kim's Personality Traits In “Searching” Movie Directed By Aneesh Chaganty". The purpose of this research is to analyze the personality of the main character David Kim. The object of research used is the movie "Searching" directed by Aneesh Chaganty and released in 2018. The movie "Searching" tells the story of a single father named David Kim who is trying to find the whereabouts of his missing daughter using technology in the form of social media. David Kim's personality that stands out in this movie is the reason why the author uses this movie as the object of research. The writer uses the Personality Traits Theory (1992) from Costa. The writer decided to use a qualitative method to find the results of this research. Based on the analysis, the writer found that there are fifty-three pieces of evidence with details from the neuroticism domain with twenty-five pieces of evidence, extraversion domain with six pieces of evidence, openness domain with one piece of evidence, agreeableness domain with eleven pieces of evidence, and conscientiousness domain with ten pieces of evidence. The most personality found in David Kim in this movie is from the neuroticism domain. The writer concludes that David Kim is a responsible and caring person, it’s just that he had a bad experience that made him lose his way. But he is a person who tries to improve himself. Suggestions from the research can include analyzing other characters, using different theories, and taking morals from this movie.